OPTIMIZATION OF PROBLEM-SOLVING STRATEGIES IN PAI LEARNING IN SCHOOLS - Amrullah, Asbi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
As a learning agents, Islamic Religious Education Teachers (GPAI) have a central role in building the quality of PAI learning. One of the factors that influence the quality of PAI learning is the selection to learnthe right learning approach by GPAI in designing and managinto learnng. Therefore, in the context of learning reform that should be carried out by PAI teachers is how to change the pattern of PAI learning activities which are dominated by the application of conventional (teacher-oriented) learning approaches to studentoriented learning approaches. One of them is a problem-solving strategy. The purpose of this research is an effort to cover GPAI skills in exploring students' abilities to think creatively, critically and rationally through problem-solving learning models and strategies. This study uses a qualitative approach to the type of library research. Sources of research data come from books, journals and scientific articles. All data obtained were analyzed with a hermeneutic scalpel. The results of this study indicate that problem-solving learning strategies can stimulate students to think creatively, critically and rationally.